Hydrogeochemical study and iron removal of groundwater in North Kelantan / Nur Hayati Hussin - Nur Hayati, Hussin (2011)
The hydrogeochemical study and iron removal of groundwater was carried out in North Kelantan Basin. This low-lying area is covered by alluvium deposits of Quaternary age. The thickness of the alluvium may reach up to 200 m to the coast. Patches of granite hills appear in the southeast part known as Bukit Marak and Bukit Kechik that belong to Boundary Range Granite. Granite and metamorphic rock are encountered as bedrocks. Kelantan River is the main drainage of the basin with 248 km long and covers an area of approximately 11900 km2. Hydrology study determined the baseflow index (BFI) of the basin as 0.54. This value is influenced by diverse geological, morphological and climatological aspects of the basin. Interaction between surface water and groundwater was found in the lower part of the basin while surface runoff dominanted the process in the upper part of the basin. The total precipitation received in the basin was 30.95 x 109 m3/year. Water loss via potential evapotranspiration was about 40% with 50% of runoff coefficient. Based on water balance study, recharge to the aquifer was estimated about 11% from the total precipitation received. The thick sequences of alluvium deposits form an aquifer system in North Kelantan. Three layers of aquifer were identified; Layers 1, 2 and 3 with depth interval of 20 m, 20 – 50 m and more than 50 m, respectively. These layers are separated by semi permeable clay layer. Layer 1 is known as a remarkable source of public water supply in the study area as groundwater has been exploited since 1935. Hydrochemical facies reveal that the NaHCO3 and NaCl facies are prevalent in the aquifer system. The evolution of groundwater is chemically governed by the process of weathering, dissolution, ion exchange and precipitation. Geochemical modeling indicates that the ferromagnesian minerals of hematite and goethite precipitate while pyrite undergones dissolution leading to an increase of iron in groundwater. The groundwater is naturally rich with iron and exceeds the WHO (2008) acceptable limit for drinking water. Presently, conventional groundwater treatment is being used to treat the groundwater for public, agricultural and industrial purposes. Ionic liquid as a medium in liquid-liquid extraction with 1,10-phenanthroline as a chelating agent was studied as an alternative method for iron removal. Successful removal of iron was achieved with more than 95% removal from the initial concentration of groundwater samples. However, more detailed research is needed before the ionic liquid is able to replace the conventional groundwater treatment as it gives a very low recovery about 25% - 60% when reused. Furthermore, due to the ion exchange process the appearance of anion of ionic liquid also has been detected in groundwater samples.